Chronic autoimmune disorders are increased in coeliac disease: A case–control study. Issue 47 (November 2017) - Bibbò, Stefano; Pes, Giovanni Mario; Usai-Satta, Paolo; Salis, Roberta; Soro, Sara; Quarta Colosso, Bianca Maria; Dore, Maria Pina
Abstract : Abstract: Coeliac disease (CD) is an autoimmune disorder of the small bowel associated with increased risk of additional autoimmune diseases (ADs). To investigate the prevalence of ADs in a population of adult coeliac patients. This was a retrospective case–control study. Data from coeliac patients and controls referred to a tertiary center between 2013 and 2016 were collected. The frequency of ADs and the unadjusted and adjusted odds ratios (ORs) for age, gender, disease duration, and body mass index with their 95% confidence intervals (CIs) were evaluated. Two hundred fifty-five patients with CD (median age 37.1 years; 206 women) were matched with 250 controls. ADs were more frequent (35.3%) in coeliac patients than in controls (15.2%). Adjusted ORs for the presence of only 1, at least 1, and more than 1 AD were 3.13 (95% CI 1.81–5.42, P < .0001), 3.31 (95% CI 2.00–5.46, P < .0001), and 3.93 (95% CI 1.49–10.36, P = .006), respectively. Hashimoto thyroiditis was the most prevalent AD (24.3% vs. 10%) OR = 2.55 (95% CI 1.39–4.70, P < .0001), followed by psoriasis (4.3% vs. 1.6%), type 1 diabetes (2.7% vs. 0.4%), and Sjögren syndrome (2.4% vs. 0.4%). These findings suggest a need for a careful surveillance of autoimmune status, especially for Hashimoto thyroiditis in patients with celiac disease.